Islamic Propaganda in the Transformation of Javanese Mystical-Islamic Society Sukowiyono Village - Hanifah Fauziah; Abdul Fadli (Budapest International Research and Critics University, 2022)
This research is a paper that discusses Islamic propaganda in the transformation of the Kejawen Mystical Society into Kejawen Islam in Sukowiyono Village during the New Order era This research begins with the phenomenon of the shift in the belief of the people of Sukowiyono Village, Before the 1968 Indonesian Communist Party Rebellion event, the majority of the people adhered to the Kejawen belief with animism and dynamism known as Kejawen Mysticism, but after the 1968 PKI rebellion all Kejawen people in Sukowiyono Village changed their beliefs to become adherents of Islam because of the practice of Islamic propaganda which was intensified by the government to eradicate the remaining communist sympathizers in Sukowiyono Village with disguised da'wah. The research method used by the author is a qualitative research method with a case study approach, with data collection techniques using observation, in-depth interviews, and documentation. The results showed that Islamic propaganda was carried out by the government because of the relationship between the Javanese community and PKI sympathizers, PKI sympathizers were affiliated with Kejawen and founded the Siti Inggil college so that they moved the government to Islamize Kejawen with the help of the Nahdlatul Ulama Islamic organization. As for the implementation of Propaganda through several activities, including by establishing langgar as a place for introduction and learning of Islam, the process uses the propaganda technique of name calling and using all forms of persuasion. propaganda techniques transfer and using all forms of persuasion. The third is the process of obtaining the KTP of the people of Sukowiyono Village, the process using the plain folks and using all forms of persuasion.